Designing Student Worksheets Based on Local Wisdom Using a Detailed Learning Model Integrated Discovery Learning on Biodiversity Material - Tomi, Dodo; Suraya, Ely; Aprianto, Riko; Sastria, Emayulia; Leoni, Lovi (International Journal of Education and Teaching Zone, 2024)
The research that has been carried out is intended to produce student worksheets, which in Indonesian are abbreviated as LKPD. for Biology Learning based on Kerinci local wisdom, which is integrated with the Discovery Learning model on biodiversity material. This research is development research using the 4D model. The subject of this research is the class used in class X SMAN 2 Kerinci which consists of small group trials (9 people) and product trials (33 people). The data collection instrument in this research was a questionnaire where, at the development stage, the student worksheets were validated by material experts and design experts and assessed through responses from biology subject teachers. The data analysis technique used in this research uses a Likert scale. The research results show that material expert validation, with a percentage of 88.33%, is in the very good category. Furthermore, the design validation results are with a percentage of 98.33% in the very good category. The research results also showed that biology teachers responded to the developed student worksheets with a percentage of 87.50% in the "very good" category. The results of the small group trial of students were 76.62% in the "good" category, while the results of the large group trial were 80.37% in the "very good" category. Based on the results of validation and field trials, the LKPD based on Kerinci local wisdom, which is integrated with the Discovery Learning learning model on biodiversity material, is good and suitable for application in biology learning, especially on biodiversity material.